Overlapping but Language-Specific Mechanisms in Morphosyntactic Processing in Highly Competent L2 Acquired at School Entry: fMRI Evidence From an Alternating Language Switching Task - Meykadeh, Simin; Golfam, Arsalan; Batouli, Seyed Amir Hossein; Sommer, Werner (Frontiers in Human Neuroscience, 2021)
Abstract is available in pdf file.